2016
DOI: 10.1080/09712119.2016.1219665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic acid blend andBacillus subtilisalone or in combination on growth traits, blood biochemical and antioxidant status in broilers exposed toSalmonella typhimuriumchallenge during the starter phase

Abstract: The present study was designed to find the effect of an antibiotic, an organic acid and a probiotic on performance traits, blood biochemical parameters and antioxidant status during the starter phase exposed to Salmonella typhimurium challenge. A total of 300 day-old broiler chicks were randomly allocated to control (basal diet), T1: infected with Salmonella enteric subsp. Typhimurium; T2: infected + avilamycin; T3: infected + organic acid; T4: infected + Bacillus subtilis; T5: infected + organic acid + probio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
89
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 20 publications
9
89
1
Order By: Relevance
“…In agreement with the present study, Mokhtari et al () reported that adding antibiotics in broiler chicken diets improves ADG in starter experimental period. By contrast, Abudabos, Alyemni, Dafalla, and Khan () suggested that the supplementation of an antibiotic did not have any effect on ADG and FCR. Avilamycin is an oligosaccharide (orthosomycin) antimicrobial substance belonging to the orthosomycin class of antibiotics, which shows bactericidal activity against gram‐positive bacteria and is used only for growth promotion (Witte, ).…”
Section: Discussionmentioning
confidence: 93%
“…In agreement with the present study, Mokhtari et al () reported that adding antibiotics in broiler chicken diets improves ADG in starter experimental period. By contrast, Abudabos, Alyemni, Dafalla, and Khan () suggested that the supplementation of an antibiotic did not have any effect on ADG and FCR. Avilamycin is an oligosaccharide (orthosomycin) antimicrobial substance belonging to the orthosomycin class of antibiotics, which shows bactericidal activity against gram‐positive bacteria and is used only for growth promotion (Witte, ).…”
Section: Discussionmentioning
confidence: 93%
“…The effect of B. subtilis on growth performance improvements by alteration of intestinal microbiota in broilers is well documented (Abudabos, Alyemni, Dafalla, & Khan, ; Aliakbarpour et al., ; Jayaraman et al., ; Jeong & Kim, ; Sen et al., ; Wu et al., ). We also demonstrated that fermented products from B. subtilis could improve growth performance and intestinal morphology in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, butyric acid, the major energy source to enterocytes, is essential to the health of intestinal mucosa (Isolauri et al 2004), and as an organic acid, it did not affect broiler chicken performance challenged with Salmonella ernerica subsp. Typhimurium (Abudabos et al 2017). On the other hand, the addition of 2 ml of Aciflex® as organic acid per litre of Japanese quails drinking water improved the performance and dressing percentage (Khan et al 2016).…”
Section: Introductionmentioning
confidence: 97%